Predictors of acceptability and emotional response to computerized neuropsychological assessments in older adults: The CogSCAN Study: Neuropsychology/computerized neuropsychological assessment. (7th December 2020) - Rossie, Matilda; Croot, Karen; Allison, Karen C.; Brodaty, Henry; Crawford, John D.; Lee, Teresa; Henry, Julie D.; Draper, Brian; Close, Jacqueline; Ong, Min Yee; Lam, Ben C. P.; Sachdev, Perminder S.; et al.
Abstract: Background: Computers and related technologies are increasingly used for cognitive assessment. However, few studies have considered older adults' experience using computerized neuropsychological assessment (CNA), or individual characteristics that may influence acceptability and emotional responses to computerized tests. Method: 205 community‐dwelling native English speakers aged 60‐95 were randomly assigned to complete two of four CNA batteries: Cogstate, CANTAB, CBS, and NIH Toolbox, on an iPad. After test completion, participants rated their emotions during testing on a Mood Adjective Checklist (MAC) with four subscales ‐ high stress (worried), low stress (relaxed), high arousal (energised), low arousal (tired), and provided ratings of test acceptability. Multiple regression analyses investigated associations of demographics (age, sex, education), cognitive level (MoCA, premorbid ability), subjective memory, mood over the past week (depression, anxiety, stress), computer/technology attitudes and experience, with the four MAC subscales and test acceptability score. Parallel analyses were performed in a subsample of participants also completing a pen‐and‐paper neuropsychological battery (PnP). Potential differences in predictors for CNA and PNP and the influence of potential confounders (PnP yes/no, CNA test pair) were examined. Result: Over half of the participants had considerable experience with computers or tablets (Table 1). Demographics were not significantly related to emotion ratings or test acceptability and were excluded from further analyses. Higher stress over the past week was associated with feeling more worried and tired during test‐taking. Higher premorbid ability was associated with feeling less relaxed (Table 2). Greater computer anxiety, higher premorbid ability and more computer experience were associated with lower CNA acceptability. Although some predictors of PnP acceptability and emotional response differed (Table 3), interactions between predictors and testing mode were non‐significant for all outcome variables (p's> .05). Inclusion of potentially confounding variables did not alter the overall findings. Conclusion: Recent mood, cognitive level, computer attitudes and experience influenced emotions during testing and test acceptability. These relationships and their potential association with CNA and PnP performance will be investigated in future work. Data on emotional response to testing and test acceptability will need to be triangulated with psychometric information about CNA and PnP measures to determine the most suitable test options for individuals.